2015
DOI: 10.1089/apc.2014.0199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HIV Outcomes for Patients Linked at Hospital Versus Community-Based Clinics

Abstract: Outpatient care for people living with HIV is delivered in diverse settings. Differences in setting may impact HIV outcomes. We evaluated HIV-infected adults in care at Ryan White-funded clinics in Philadelphia, PA, between 2008 and 2011 to determine how setting of care (hospital versus community-based) influenced HIV outcomes. Clinics were categorized as hospital-based if they were located onsite at a hospital. The composite outcome was completion of the final three steps of the HIV care continuum: (1) retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
1
6
1
Order By: Relevance
“…Interestingly, we also observed differences by clinic type with participants at community-based clinics having more regular VL monitoring and better retention in care than those enrolled at hospital-based clinics. This observation differs from that of other studies that did not find meaningful differences in retention with respect to clinic type [ 38 , 39 ]. Further exploration of patient characteristics by site, as well as characterization of care delivery such as the receipt of primary care and availability of ancillary services at each site, as well as the costs of providing these services, is necessary to fully understand the implications of these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, we also observed differences by clinic type with participants at community-based clinics having more regular VL monitoring and better retention in care than those enrolled at hospital-based clinics. This observation differs from that of other studies that did not find meaningful differences in retention with respect to clinic type [ 38 , 39 ]. Further exploration of patient characteristics by site, as well as characterization of care delivery such as the receipt of primary care and availability of ancillary services at each site, as well as the costs of providing these services, is necessary to fully understand the implications of these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Compared with those studies using the data from major health care facilities, such as urban hospitals, our study showed similar clinical outcomes. This finding suggests that the HIV care can be delivered effectively in community settings, which was also supported by the research conducted in other settings [35, 36].…”
Section: Discussionsupporting
confidence: 74%
“…Schranz et al examined how the care setting, hospital versus community-based, influences the HIV care continuum 20 . The study included patients >18 years cared for in 25 HIV clinics (12 hospital based, 13 community based) in Philadelphia from 2008–2011.…”
Section: Resultsmentioning
confidence: 99%
“…There are likely differences in the approaches to YLHIV for providers from different training backgrounds, as seen in non-HIV states such as sickle cell, cystic fibrosis, and end stage renal disease 16,17 . Further, clinics can vary in terms of location (urban versus rural, community versus academic) 1820 . These potential provider and clinic differences may result in different outcomes among YLHIV in different settings.…”
Section: Introductionmentioning
confidence: 99%